The Admission (Neutrophil+Monocyte)/Lymphocyte Ratio Is an Independent Predictor for In-Hospital Mortality in Patients With Acute Myocardial Infarction - Wang, Yu; Yuan, Miao; Ma, Yao; Shao, Congcong; Wang, Yuan; Qi, Mengyao; Ren, Bincheng; Gao, Dengfeng (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Peripheral differential leukocyte counts are accepted prognostic indicators in patients with acute myocardial infarction (AMI). Herein, we assessed the value of the admission (neutrophil + monocyte)/lymphocyte ratio (NMLR) in predicting in-hospital mortality in these patients. Materials and Methods: Samples of patients from the Medical Information Mart for Intensive Care Ⅳ (MIMIC-Ⅳ) database meeting the criteria were included. Receiver operating characteristic (ROC) curves were plotted to explore the predictive value and the optimum cut-off value of admission NMLR. Univariate and multivariate Cox regression analyses and restricted cubic spline (RCS) were performed to determine and visualize the association between admission NMLR and in-hospital mortality. The Kaplan-Meier (KM) method was used to plot survival curves of two groups with different admission NMLR levels. Results: Samples in the non-survival group had higher admission NMLR values than samples in the survival group (12.11 [7.22-21.05] vs. 6.38 [3.96-11.25], P < 0.05). The area under the ROC curve (AUROC) [0.707 (95% Confidence Interval, 0.677-0.737)] was significantly better than those of other indicators related to peripheral differential leukocyte counts, and the optimal cut-off value was 8.518. Cox regression analysis identified that higher admission NMLR was an independent risk factor for in-hospital mortality. RCS visualized the uptrend and the nonlinear relationship between admission NMLR and in-hospital mortality (P-value for nonlinearity <0.05). The KM survival curve of the high admission NMLR group was significantly lower than that of the low admission NMLR group (P < 0.001), and the former was associated with an increased risk of in-hospital mortality compared to the latter (Hazard Ratio, 1.452; 95% Confidence Interval, 1.132-1.862; P <0.05). Conclusions: An elevated admission NMLR is an independent predictor for high in-hospital mortality in patients with AMI. And it is superior to other leukocyte-related indexes.